Mastering autocad 2006 and autocad LT 2006 - Omura, George (Sybex, 2005)
Mastering AutoCAD 2006 and AutoCAD LT 2006 teaches AutoCAD and AutoCAD LT essentials using concise explanations, focused examples, step-by-step instructions, and hands-on projects. This detailed resource works as both a tutorial and stand-alone reference. Part I introduces the basics of the interface and drafting tools; Part II moves into such intermediate skills as effectively using hatches, fields, and tables; Part III details such advanced skills as attributes, dynamic blocks, drawing curves and solid fills; Part IV explores 3D modeling and imaging; and Part V discusses customization and integration. The CD includes all the project files necessary for the tutorials, a trial version of AutoCAD, and five chapters of advanced material on such topics as Active X and VBA.